VD_FINDINFO HC / 2015 / 685 vom 2. Juni 2015 - VD Tribunal cantonal (2015)
RETRAITVOIE DE DROIT, FRAIS JUDICIAIRES, FRAIS D'EXPERTISE, RÉPARTITION DES FRAIS | 106 al. 1 CPC (CH), 110 CPC (CH), 241 CPC (CH)